The Readiness of University to Implement of Merdeka Belajar Kampus Merdeka (MBKM) as a Competitve Advantage at Tridinanti University Palembang: - - Irayani Irayani; Mimi Kurnianengsih; Ima Andriyani (Ma Chung Press, 2022)
This article aims to identify the challenges faced by higher education and the implementation of free learning during the Covid-19 pandemic, and considers that the main approach to establish Tridinanti University is the implementation of “Independent Learning – Independent Campuses (MBKM)”. The logical consequence of this transition will require innovation not only in digital tools and forms of learning, but also in the learning process and in the learning experience of students. The